THE INCORRECT USE OF TENSES IN STUDENTS’ JOB TRAINING REPORT - Reny Juliana; Asti Purbarini; Irfan Iskandar (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2020)
Vocabulary plays an important role in learning a foreign language. In order to communicate well in a foreign language, students should learn adequate number of words and should know how to use them accurately (Huyen & Nga, 2003). Moreover, students usually feel bored quickly as teachers often use conventional methods of teaching especially in teaching vocabulary (Zou, Wang, Xie, & Kohnke, 2018). This study was investigating the students’ cognitive engagement in learning vocabulary throughEducard media. The objectives of this study was to find out the way Educard facilitated the students’ cognitive engagement in learning vocabulary through Educard and students’ responses. The participant of this research is students of eighth grade in one of junior high school.This study used qualitative approach. The data were collected by distributing the questionnaire, interview to 5 students of eighth grade and documentation. To analyze the data, this research adopted Miles, Huberman Saldaña (2014) techniques; data collection, reduction, display and verification. It showed students are facilitated by using Educard as learning mdia to learn vocabulary and engage them cognitively. There are many kind of cognitive engagement has been engaged in their learning while using Educard to learn English vocabulary such as : self- regualted learning, resource management, recepience and taks focus. Moreover, Educard build them cognitive activities in learning vocabulary. Keywords:Students’ cognitive engagement, Vocabulary, Educard